Rancangan Buku Saku Serangga Polinator Sebagai Penunjang Pembelajaran Biologi di Bakal Sekolah Alam Kampung Wisata Isyo Hils Rhepang Muaif Nimbokrang, Jayapua - Ramandey, Euniche R.P.F.; Warikar , Evie Lilly (Jurusan Biologi FMIPA Universitas Cenderawasih, 2023)
Abstract The learning media for the identification of pollinator insects is deemed necessary to be distributed through socialization and practice for elementary school children, and teachers at the “Isyo Hills” Nature School in Kampung Rhepang Muaif. Directly arouse interest and enthusiasm for learning for elementary school children at the Nature School